18 Describing treatment aims for patients approaching the end-of-life: mapping concepts from a scoping study of the medical literature. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Qureshi, SP; Dewar, A
Abstract : Background: Learning to care for patients approaching the end-of-life may be complicated by inconsistent language and lack of clear terms to discuss aims of treatments. To begin the process of developing a clear taxonomy for end-of-life care education, it is necessary to first establish the breadth of terms in use, and consider concepts they represent. This study aimed to map the scope of concepts utilised in discussion of treatment for patients approaching the end-of-life in medical literature. Methods: The authors undertook a scoping study of literature existing for the clinical education or professional development of medical doctors. This incorporated a systematic search of academic databases and non-database websites, and iterative development of inclusion criteria. Inductive qualitative content analysis was undertaken of the 269 included documents to examine terms, and their explicit and implicit meanings. Results: As analysis progressed, terms were grouped into one of three emerging over-arching categories according to the concepts represented. One of these major categories consisted of concepts for possible aims of care for patients approaching the end-of-life: Palliative care; End-of-life care; Advance care planning; Assessment of dying patients; Withdrawing treatment; Active treatment; Do Not Attempt Cardiopulmonary Resuscitation; Supportive Care; Preferred Place of Care; Medicalised Death; Conservative treatment; Advanced decision to refuse treatment; Curative change agents; Escalating medical care; Overtreatment. Interpretation and discussion of these concepts will be presented, including how they interrelate with or contradict one another. Conclusions: This study has delineated overlapping concepts in medical literature related to treatment aims for patients approaching the end-of-life. It has highlighted lack of consistent language. Further work is needed to develop clearly defined terms for teaching that can be widely understood and agreed upon.